The Grand Design - Stephen Hawking (Bantam Books, 2010)
When and how did the universe begin? Why are we here? Is the apparent 'grand design' of our universe evidence for a benevolent creator who set things in motion? Or does science offer another explanation? In The Grand Design, the most recent scientific thinking about the mysteries of the universe is presented in language marked by both brilliance and simplicity. Model dependent realism, the multiverse, the top-down theory of cosmology, and the unified M-theory - all are revealed here. This is the first major work in nearly a decade by one of the world's greatest thinkers. A succinct, startling and lavishly illustrated guide to discoveries that are altering our understanding and threatening some of our most cherished belief systems, The Grand Design is a book that will inform - and provoke - like no other.